AB1021 Prevalence and Neuroimaging Correlates of Central Ataxia In Childhood-Onset Systemic Lupus Erythematosus. (9th June 2015) - Lapa, A.T.; Barbosa, R.; Mendonça, I.N.; Souza, M.C.F.; Peres, F.A.; Marini, R.; Rittner, L.; França, M.; Bergo, F.; Cendes, F.; Appenzeller, S.
Abstract : Background: Childhood-onset systemic lupus erythematosus (cSLE) is a chronic autoimune disease with fluctuating disease activity. Neurospichiatric manifestations are common and vary from common manifestations such as headache and anxiety to life threatening manifestations such as acute confusional syndrome. Ataxia has not been studied frequently in cSLE. Objectives: To determine the prevalence of ataxia in cSLE and clinical, laboratory and treatment features associated with its occurrence. To determine neuroimaging features associated with ataxia, especially medullary area and cerebellar volume. Methods: We included 62 cSLE patients followed at the State university of Campinas and 28 healthy controls with similar age and gender distribution. All patients and controls were evaluated for ataxia using Scale for the assessment and rating of ataxia (SARA), validated in portugues. All subjects realized magnetic resonance imaging using a 3 tesla scanner (Phillips). Sagittal T1 1mm thick slices were used for analysis. Medullary area and excentricity and cerebellar volume were analyzed using semiautomatic computer segemntation software (SpineSeg and Neuroline). Results: We observed ataxia in 22 out of 62 (35.5%) patients and in none of the controls (p=0.002). Ataxia was associated with the presence of neuropsychiatric manifestations (p=0.003) and antifosfolipid antibodies (p=0.005). None of the other clinical, laboratory or treatment features were associated with ataxia. Medullary area was significant smaller in cSLE when compared to controls (p=0.002). Reduction of medullar area was associated with cumulative corticosteroid dose (r=-0.43; p=0.008) and the presence of ataxia (p=0.003). Cerebellar volume was significantly reduced in cSLE patients when compared to controls (p<0.001). Cerebellar atrophy was associated with medullary area (r=0.46; p=0.001). None of the other clinical, laboratory and treatment features were associated with cerebellar volume. Conclusions: Ataxia is frequently observed in cSLE and associated with neuropsychiatric manifestations and antiphospholipid antibodies. Neuroimaging features, especially medullary volume is associated with ataxia and cerebellar atrophy may be secondary. Disclosure of Interest: None declared